Vaccines for Streptococcus agalactiae: current status and future perspectives - Pena, João Matheus Sobral; Lannes-Costa, Pamella Silva; Nagao, Prescilla Emy (Frontiers in Immunology, 2024)
A maternal vaccine to protect newborns against invasive Streptococcus agalactiae infection is a developing medical need. The vaccine should be offered during the third trimester of pregnancy and induce strong immune responses and placental transfer of protective antibodies. Polysaccharide vaccines against S. agalactiae conjugated to protein carriers are in advanced stages of development. Additionally, protein-based vaccines are also in development, showing great promise as they can provide protection regardless of serotype. Furthermore, safety concerns regarding a new vaccine are the main barriers identified. Here, we present vaccines in development and identified safety, cost, and efficacy concerns, especially in high-need, low-income countries.